Cricoid pressure controversies - Kaur, Harpreet; Pareek, Ravi; Harsh, Harsh Kumar; Shukla, Veena; Tulsyan, Nitin (International Journal Of Community Medicine And Public Health, 2020)
Rapid sequence induction (RSI) is a common technique used in clinical anaesthesia to prevent pulmonary aspiration of gastric contents. Sellick introduced this in 1961. However, scientific validation to show the advantage of this technique in preventing aspiration is limited in literature. Numerous researches have shown that cricoid pressure (CP) application might have no benefit in preventing aspiration. Additionally this could lead to problems in securing the airway. Proper teaching and regular training sessions of this technique are mandatory in routine anaesthesia practice.